The Correlation Between Online Games and English Vocabulary Acquisition of English Language Education Students - Setiawan, Muhammad Asraf; Korompot, Chairil Anwar; Sofyan, Ryan Rayhana (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research examines the correlations between online games and English vocabulary acquisition. It implements a quantitative research design, where there are two instruments were used, an online questionnaire and a vocabulary assessment form. In this research, the English education students of Universitas Negeri Makassar were selected with the amount of 30 students. Both of the quantitative data were collected using Google Forms and analyzed using SPSS v.15. The result of the research data analysis shows that the correlation coefficient between the intensity of playing online games and English vocabulary acquisition is 0.759, which is interpreted as a moderate positive correlation. This means that as the intensity of online games increases, there is a moderate tendency for English vocabulary acquisition to increase.Keywords: English education, vocabulary acquisition, online games